Crisis and Risks in Engineering Project Management: A Review - Alves, Josivan Leite; Ferreira, Edivan Alexandre; Nadae, Jeniffer de (Brazilian Journal of Operations & Production Management, 2021)
Goal: This paper performs a literature review to identify and analyze the main gaps related to crisis management and risk management in the engineering projects context. Design / Methodology / Approach: A literature review research design was carried out merging bibliometrics, network and qualitative and quantitative content analysis. Data were obtained from the scientific database Scopus. Results: Publications per year illustrates that in 2016 as concentrated the major number of papers. Only 1% of the authors published 4 papers about models for software engineering risks analysis and reduction. The paper distribution by country shows that the United States has the highest percentage, about 16% of the total. The network of co-occurrence of all keywords has three well-defined clusters. Limitations of the investigation: The quantity of papers analyzed and the selection of a single database. Practical implications: This research encourages project managers to develop pertinent skills for crisis management and risk management in the engineering projects context. Furthermore, this study can guide decision-makers on how to manage risks during the crisis, and also highlights the importance of creating a lessons learned database. Originality / Value: The current study can contribute to companies catching lessons learned from literature, helping project managers to motivate the team during the crisis scenarios, to perform an effective struggle during the crisis, and to turn to the former position in a short time after the crisis.